2006
DOI: 10.1111/j.1743-6109.2006.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Freeze‐dried platelet‐rich plasma shows beneficial healing properties in chronic wounds

Abstract: Fresh platelet concentrates are used in many centers to treat recalcitrant wounds. To extend the therapeutic shelf-life of platelets, we analyzed the wound-healing effects of fresh-frozen and freeze-dried (FD) platelet-rich plasma (PRP) using a diabetic mouse model. Db/db mice with 1.0 cm2 dorsal excisional wounds (n = 15/group) were treated with a single application of FD PRP (1.2 x 10(6) platelets/microL) with or without a stabilization solution, and compared with wounds treated with fresh-frozen, sonicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 33 publications
8
99
0
2
Order By: Relevance
“…PRP has been demonstrated to be effective in bone regeneration, wound healing, and improvement of musculoskeletal sports injuries. [9][10][11][12][13][14][15] Recently, clinicians extended the scope of PRP therapy to soft tissue augmentation by combining PRP with fat grafting. Although some successful clinical results were reported, 16,17 evidence supporting the application of PRP combined with fat grafts in soft tissue augmentation remains limited, as only a few basic research and preclinical studies in small animals have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…PRP has been demonstrated to be effective in bone regeneration, wound healing, and improvement of musculoskeletal sports injuries. [9][10][11][12][13][14][15] Recently, clinicians extended the scope of PRP therapy to soft tissue augmentation by combining PRP with fat grafting. Although some successful clinical results were reported, 16,17 evidence supporting the application of PRP combined with fat grafts in soft tissue augmentation remains limited, as only a few basic research and preclinical studies in small animals have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…There have been human studies to report that PRP has a positive effect on wound healing [12][13][14][15] . In animal studies, histological examinations revealed enhanced fibroblastic and endothelial cell formation during wound healing, increased neovascularization [12,[19][20][21][22] , and enhanced granulation tissue formation [12,19,21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…There are many cases reported in different studies showing encouraging trends for PRP to be used as local application in the form of gel for promoting the healing of chronic wounds. But all these studies have used PRP as local application, adjunct to standard ulcer management [29,30]. However, these gels are expensive.…”
Section: Discussionmentioning
confidence: 99%
“…These growth factors aid healing by attracting un-differentiated cells in the newly formed matrix and triggering cell division. PRP may suppress cytokine release and limit inflammation, interacting with macrophages to improve tissue healing and regeneration, promote new capillary growth, and accelerate epithelialization in chronic wounds [29,30].…”
Section: Properties Of Platelet-rich Plasma Towards Wound Healing Andmentioning
confidence: 99%